2020
DOI: 10.1002/admi.202000419
|View full text |Cite
|
Sign up to set email alerts
|

Ion Selective Transport of Alkali Ions through a Polyelectrolyte Membrane

Abstract: The ionic conductivity of a polyelectrolyte membrane consisting of 30 bilayers of poly(allylamine hydrochloride) and p‐sulfonato‐calix[8]arene, (PAH/calix8)30, is investigated for two alkali ions, i.e., Li+ and Rb+. Two different transport pathways, a fast and a slow one, are identified for Li+ transport. By contrast, only the fast transport pathway is observed for Rb+ transport. This fast transport pathway is assigned to regular hopping through bulk material, whereas the slow transport pathway originates from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…In 2020, Weitzel et al 44 prepared a polyelectrolyte membrane consisting of 30 bilayers of poly(allylamine hydrochloride) and p-sulfonato-calix [8]arene, (PAH/calix8) 30 , in which poly(allylamine hydrochloride) was used as a polycation and calixarene as the anion, and explored the transport rate of alkali ions on this polyelectrolyte membrane. It was found that Li + has two different transport pathways, and the larger Rb + ions have only fast transport paths.…”
Section: Calixarene-based Membranesmentioning
confidence: 99%
“…In 2020, Weitzel et al 44 prepared a polyelectrolyte membrane consisting of 30 bilayers of poly(allylamine hydrochloride) and p-sulfonato-calix [8]arene, (PAH/calix8) 30 , in which poly(allylamine hydrochloride) was used as a polycation and calixarene as the anion, and explored the transport rate of alkali ions on this polyelectrolyte membrane. It was found that Li + has two different transport pathways, and the larger Rb + ions have only fast transport paths.…”
Section: Calixarene-based Membranesmentioning
confidence: 99%
“…[13,18,19] Polyelectrolytes are appealing for programming the ionic nanopore transport based on the i) possibility of binding ions to themselves (ion-or ligand-binding), [5,6,13,20] ii) ability to vary the wettability of the membrane surface as well as the nanopores, [13,21,22] and also iii) possibilities to change the charge density in the pore sites gradually. [23,24] However, literature still seeks experimental studies explaining the role of polyelectrolyte absence/presence on the ligand-binding in confined space. Theoretical literature in recent years focused on explaining how polyelectrolyte functionalization in nanoconfinement (e.g., inside nanopores or around nanoparticles) affects the binding equilibrium between ligand and receptors.…”
Section: Introductionmentioning
confidence: 99%